Contingent convertible bonds issuance announcement effect on Asian bank prices : Empirical evidence - Tan, Yujing (2017)
This study examines the announcement effect of contingent convertible bonds issue made by Asian banks on issuer banks’ share price and CDS spread. Announcement of contingent convertible bonds issuance is found to have a generally negative impact on issuer banks’ share price. Significant stock price reactions are observed on the second, fourth and tenth day after the announcement is made, indicating some lag in the market response towards the announcement. Furthermore, this study also finds that the design of contingent convertible bonds has significant impact on abnormal stock returns on the announcement day. Positive abnormal stock returns will be reduced if the contingent convertible bonds have large issue size, are classified as Additional Tier 1 capital and have conversion-to-equity provisions. On the other hand, a longer time span between announcement date and issue date is find to have positive correlation with abnormal stock return. Additionally, in contrast to earlier findings, this study finds a generally positive reaction on CDS spread towards the announcement. As previous studies have used global banks’ issuance as sample, this study is the first study on contingent convertible bonds announcement effect that has segregated the issuance made by Asian banks from issuance made by issuer banks from Europe regions. This study also shows different results compared to previous studies which did not segregate between Asian and Europe issuer banks.